Globalisation, industrial diversification and productivity growth in large European R&D companies - Michele Cincera; Julien Ravet (European Commission, Joint Research Centre (JRC), 2011)
This paper aims to assess the impact of both geographic and industrial diversification of economic activities on the productivity performance of large European R&D Multinational Enterprises (MNEs). Based on the worldwide subsidiaries of these firms, we measure the performance of the firms according to their level of industrial diversification and globalisation that we proxy with the presence and importance of subsidiaries in the EU, North America and Asia-Pacific regions. The sample consists of large R&D firms that represent about 80% of total European R&D. In general, the results indicate a positive impact from globalisation on firms' R&D productivity, especially in the US, while a negative impact for industrial diversification is found.
Keywords: O33; 330; R&D; European MNEs; productivity; globalisation; industrial diversification